Pupil diameter covaries with BOLD activity in human locus coeruleus. Issue 8 (7th February 2014) - Murphy, Peter R.; O'Connell, Redmond G.; O'Sullivan, Michael; Robertson, Ian H.; Balsters, Joshua H.
Abstract The locus coeruleus‐noradrenergic (LC–NA) neuromodulatory system has been implicated in a broad array of cognitive processes, yet scope for investigating this system's function in humans is currently limited by an absence of reliable non‐invasive measures of LC activity. Although pupil diameter has been employed as a proxy measure of LC activity in numerous studies, empirical evidence for a relationship between the two is lacking. In the present study, we sought to rigorously probe the relationship between pupil diameter and BOLD activity localized to the human LC. Simultaneous pupillometry and fMRI revealed a relationship between continuous pupil diameter and BOLD activity in a dorsal pontine cluster overlapping with the LC, as localized via neuromelanin‐sensitive structural imaging and an LC atlas. This relationship was present both at rest and during performance of a two‐stimulus oddball task, with and without spatial smoothing of the fMRI data, and survived retrospective image correction for physiological noise. Furthermore, the spatial extent of this pupil/LC relationship guided a volume‐of‐interest analysis in which we provide the first demonstration in humans of a fundamental characteristic of animal LC activity: phasic modulation by oddball stimulus relevance. Taken together, these findings highlight the potential for utilizing pupil diameter to achieve a more comprehensive understanding of the role of the LC–NA system in human cognition. Hum Brain Mapp 35:4140–4154, 2014. © 2014 Wiley Periodicals, Inc.